IFN gamma regulates proliferation and neuronal differentiation by STAT1 in adult SVZ niche - Gómez, Leticia P.; Medina, Rebeca; Baena, Miguel; Planas, Anna M.; Pozas, Esther (Frontiers in Cellular Neuroscience, 2015)
The adult subventricular zone (SVZ) is the main neurogenic niche in normal adult brains of mice and rats. Interferon gamma (IFNγ) has somewhat controversially been associated with SVZ progenitor proliferation and neurogenesis. The in vivo involvement of IFNγ in the physiology of the adult SVZ niche is not fully understood and its intracellular mediators are unknown. Here we show that IFNγ, through activation of its canonical STAT1 pathway, acts specifically on Nestin+ progenitors by decreasing both progenitor proliferation and the number of cycling cells. In addition, IFNγ increases the number of neuroblasts generated without shifting glial fate determination. The final result is deficient recruitment of newborn neurons to the olfactory bulb, indicating that IFNγ-induced stimulation of neuronal differentiation does not compensate for its antiproliferative effect. We conclude that IFNγ signaling via STAT1 in the SVZ acts dually as an antiproliferative and proneurogenic factor, and thereby regulates neurogenesis in normal adult brains.